2013
DOI: 10.4161/hv.25217
|View full text |Cite
|
Sign up to set email alerts
|

Particle based vaccine formulations for transcutaneous immunization

Abstract: Vaccine formulations on the basis of nano- (NP) or microparticles (MP) can solve issues with stabilization, controlled release, and poor immunogenicity of antigens. Likewise transcutaneous immunization (TCI) promises superior immunogenicity as well as the advantages of needle-free application compared with conventional intramuscular injections. Thus the combination of both strategies seems to be a very valuable approach. However, until now TCI using particle based vaccine formulations has made no impact on med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…To elucidate this topic further, a larger range in particle size should be investigated in the future. As for the controls, the amount detected in the hair follicle of free CP in an ethanolic solution and free CP in HG, with and without the application of massage, was below the lower limit of quantification (LLOQ) for both experimental setups and thus negligible [19,29,39]. This confirms that by means of encapsulation a more targeted delivery to the hair follicle was achieved.…”
Section: Follicular Uptake Of Clobetasol-loaded Nanocapsules and Contsupporting
confidence: 58%
“…To elucidate this topic further, a larger range in particle size should be investigated in the future. As for the controls, the amount detected in the hair follicle of free CP in an ethanolic solution and free CP in HG, with and without the application of massage, was below the lower limit of quantification (LLOQ) for both experimental setups and thus negligible [19,29,39]. This confirms that by means of encapsulation a more targeted delivery to the hair follicle was achieved.…”
Section: Follicular Uptake Of Clobetasol-loaded Nanocapsules and Contsupporting
confidence: 58%
“…Furthermore, antigen encapsulated in IMSG NPs turned out to be much more immunogenic (85 ± 5%) in comparison to our previously described antigen-loaded chitosan-PLGA NPs (65 ± 5%) when analyzed using ELISA [12]. Adjuvants play a vital role in vaccine development, as they increase immunogenicity of weak antigens as well as decrease the dose of the antigen required in vaccine formulations [3]. In this study we explored the possibility of improving the performance of the formulations by using c-di-AMP, since preliminary studies suggested that c-di-AMP was compatible with the nanoparticle-based platform.…”
Section: Discussionmentioning
confidence: 77%
“…by dispersing protein into an organic solution of surfactants and subsequently freeze drying them before introducing them into polymer solutions for tissue engineering. Administration of antigen solutions and particulate carriers by intradermal (ID) and intranasal (IN) routes has been widely studied [3,9]. However, recent attention focuses on non-invasive transcutaneous vaccination strategies.…”
mentioning
confidence: 99%
“…Transcutaneous immunization (TCI), another needle-free vaccination method, has been widely reviewed[144-147]. Transcutaneous delivery can lead to comparable or better efficacy than traditional injection, as seen with a trivalent inactivated influenza vaccine with heat-labile enterotoxin from Escherichia coli (LT) as an adjuvant in a dry patch[148].…”
Section: Introductionmentioning
confidence: 99%